2010
DOI: 10.1080/03235400701652508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biocontrol agent, plant extracts and safe chemicals in suppression ofMungbean Yellow Mosaic Virus(MYMV) in black gram (Vigna mungo)

Abstract: Pseudomonas fluorescens (Pf1), plant extract and bioactive compound treatments on induction of peroxidase (PO), polyphenol oxidase (PPO), phenylalanine ammonia-lyase (PAL) and accumulation of phenolics in black gram to suppress the natural incidence of Mung bean yellow mosaic bigeminivirus (MYMV) was studied. Leaf extracts of Mirabilis jalapa, Datura metel and neem (Azadirachta indica) oil provided reduced incidence of MYMV with increased yield in black gram under field conditions. The bio-compatible products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Ltd. and plant extracts were prepared in the laboratory. The plant extracts were prepared by following the method of Venkatesan et al [ 24 ]. The mature leaves (1000 g each) neem ( Azadirachta indica ) and Eucalyptus ( Eucalyptus camaldulensis ) were homogenized independently in pre-chilled mortar and pestle and through applying chilled sterilized distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Ltd. and plant extracts were prepared in the laboratory. The plant extracts were prepared by following the method of Venkatesan et al [ 24 ]. The mature leaves (1000 g each) neem ( Azadirachta indica ) and Eucalyptus ( Eucalyptus camaldulensis ) were homogenized independently in pre-chilled mortar and pestle and through applying chilled sterilized distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, the POD of T2 plants was down-regulated with a relative expression level of 0.672-fold change lower than control (Figure 7). It was observed that the induction of POD resulted in an increase of chlorophyll content and enhanced plant resistance against mungbean yellow mosaic virus and TMV [81,82]. In addition, foliar application of Ag NPs exhibited an improvement in releasing ROS and increasing antioxidant enzymes in virally infected plant tissues [36,37].…”
Section: Transcriptional Levels Of Defense-related Genesmentioning
confidence: 99%
“…The potential of plant extracts to induce systemic resistance and inhibit viral replication could be due to their high content of flavonoids and phenolic acids, and it might explain their antioxidant activity and antimicrobial efficacy [8]. Additionally, it was reported that the application of plant extracts was associated with the induction of pathogenesis-related proteins, phenylalanine ammonia-lyase (PAL), peroxidase (POD), and polyphenol oxidase (PPO) upon viral infection [15]. However, this field is still insufficiently explored, necessitating more data to comprehensively understand the different mechanisms by which these plant extracts act as antiviral agents.…”
Section: Introductionmentioning
confidence: 99%